(3TQM GdeZfj aj CUhd Gdabg GdMfais - (3CHh eMeO efUhQ Hf CMeO GdeDjO GdNhGQRei GdbGAGfis; (3LdGd GdOjf YeQ Hf eMeO Hf YeQ GdNHGRj GdMfaj,J (B671 (3g` s ((3eMeO YHO GdUeO Hf eMeO GdGOQjSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JLdi Ydi YHGOg GdeNdUjf Yf GdTQc GdNai hHYO deG cGf GdeDefhf CahI hGdCNhI JbJVi GdTabI hGdGjKGQ R s
(3BNQgG (B:s
(3LYdgeG eLGRkG YfgeG Chdi ef LYdgG eLGRkG Yf ZjQgG hGdMeO ddg hMOg s
(3GdfSNI HgG MhGTs
(3Jedc YHO GdQMje eMehO RGOgs
(3hai Chdg agQS HGdehVhYGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3MGdI GdfSNI eJhSWI s
Keywords: (3eJaQbGJs